2012
DOI: 10.1111/aen.12006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of five sampling methods for detection of the tomato potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Psylloidea: Triozidae)

Abstract: One of the challenges in detecting a pest incursion is the selection of an appropriate sampling technique that is relatively easy to use and inexpensive. Five sampling techniques (sticky traps, water traps, sweep netting, vacuum sampling and direct searching) were used to detect the tomato potato psyllid (Bactericera cockerelli) in potato crops on the North Island of New Zealand. Sticky traps and water traps outperformed the other methods in detecting psyllids. There was weak evidence that water traps outperfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As predicted by Yen et al . (), yellow sticky traps used in this study to monitor for B. cockerelli incursions were also attractive to a large number of native species, thus requiring careful identification. However, as only 0.3% of all Psylloidea caught belonged to the family Triozidae, the vast majority of specimens could rapidly be discounted as B. cockerelli based on the branching of the forewing basal vein, which is trifurcate in the Triozidae and bifurcate in all other Psylloidea families (Hollis ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As predicted by Yen et al . (), yellow sticky traps used in this study to monitor for B. cockerelli incursions were also attractive to a large number of native species, thus requiring careful identification. However, as only 0.3% of all Psylloidea caught belonged to the family Triozidae, the vast majority of specimens could rapidly be discounted as B. cockerelli based on the branching of the forewing basal vein, which is trifurcate in the Triozidae and bifurcate in all other Psylloidea families (Hollis ).…”
Section: Discussionmentioning
confidence: 99%
“…Conducting trapping studies in New Zealand, Yen et al . () found that yellow sticky traps outperformed all other methods tested for the detection of B. cockerelli in potato crops (sweep netting, vacuum sampling and direct searching) except water traps. Yellow sticky traps were also more effective at detecting low, early season populations of B. cockerelli than direct visual searches (Cameron et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adults were sampled using an inverted leaf blower (Toro® Powervac™; Anderson, SC) for 5 min, as described by Yen et al (2013). In addition, following Goolsby et al (2007), leaf samples (n=10) were collected randomly to detect potato psyllid eggs and nymphs.…”
Section: Sampling Insects and Tubersmentioning
confidence: 99%
“…Early pest detection requires a more systematic approach, especially in large farms. Traps are arguably the most widely adopted tool for systematic pest monitoring [4,5]. If implemented properly, this kind of device can successfully sample insect populations over the entire area of interest.…”
Section: Introductionmentioning
confidence: 99%